ANALISIS PERAN AUDIT FORENSIK DALAM MENGUNGKAP FRAUD PADA PENGELOLAAN DANA BANTUAN SOSIAL DI MASA PANDEMI COVID-19 - Febri Br Hutabarat; Maya Wulandari; Putri Kemala Dewi Lubis; Tina Angelia (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Forensic audits have a crucial role in uncovering fraud in the management of social assistance funds during the COVID-19 pandemic. Through a quantitative approach using secondary data from previous research and literature studies, the research analyzes the effectiveness of forensic audits in identifying fraud, including inflating the number of aid recipients and diverting funds. The findings show that forensic audits provide a systematic framework for uncovering fraud patterns. The main aim of this research is to determine and analyze the effectiveness of the use of social assistance funds during COVID-19 and detect fraud in the form of fraud therein. The results of this research emphasize the important role of forensic audits in maintaining the integrity and public trust in government social assistance programs, especially during times of crisis such as the COVID-19 pandemic.